Ultrasonography‐detected subclinical inflammation in patients with hand osteoarthritis and established rheumatoid arthritis: a comparison between two different pathologies using the same ultrasound examination protocol. (4th May 2017) - Hussain, Sidra; Sivakumaran, Priyanka; Gill, Anna; Dhas, Delfin; Ciurtin, Coziana
Abstract: Objectives: A recent review of ultrasound (US) studies in osteoarthritis (OA) showed very limited data about hand OA. Previous US studies in patients with OA described a degree of overlap between the US appearance of rheumatoid arthritis (RA) and OA joints. The present study aimed to assess the US features of subclinical inflammation in RA and hand OA, using the same US examination protocol. Methods: A retrospective, cohort study compared patients with established RA ( n = 224) and hand OA ( n = 73), with respect to several demographic, clinical, laboratory and US parameters. We used a 22‐hand joint US examination protocol (wrists, metacarpophalangeal and proximal interphalangeal joints bilaterally – Outcome Measures in Rheumatology Clinical Trials [OMERACT] scoring system) for all patients. Results: Subclinical joint inflammation in the context of equivocal clinical examination was found in 9.6% of OA patients compared with 46.4% of RA patients ( p = 0.0001), despite the fact that there was no significant difference between the degree of chronic joint swelling (synovial hypertrophy grades 2 and 3; p = 0.75 and p = 0.11, respectively). The presence of osteophytes was more common in patients with hand OA, as expected ( p = 0.0001). Conclusions: Our study findings reflected differences between the incidence and characteristics of subclinical inflammation in patients with RA and OA, which could be helpful in patients with an equivocal clinical examination or history of both diseases. Almost one in 10 patients with hand OA had active synovitis, while almost one in two patients with RA had uncontrolled inflammation in at least one joint.